The Role of Adolescents in Preventing Non-Communicable Diseases - Afifah Viramita; Ning Arti Wulandari; Ulfa Husnul Fata; Yeni Kartika Sari (Dewan Pimpinan Daerah Persatuan Perawat Nasional Indonesia Kota Blitar, 2026)
The incidence of Non-Communicable Diseases (NCDs) is predicted to reach 52 million people in 2030, which has an impact on decreasing the productivity and quality of the nation's generation. Early intervention through the role of community nurses is very necessary, especially in adolescent groups in Islamic boarding schools. This activity aims to increase preventive awareness and early detection capabilities of NCDs in students through promotive and preventive efforts. This research method uses a Pre-Experimental method with a One Group Pretest, Posttest design. From a population of 80 students and 9 health cadres of students in